2019
DOI: 10.35229/jaes.565282
|View full text |Cite
|
Sign up to set email alerts
|

The Length–Weight Relationship and Condition Factor of a Non-Native Fish Species: Striped Sea Bream (Lithognathus mormyrus L., 1758) in the Black Sea

Abstract: In this study, length-weight relationship and condition factor of Lithognathus mormyrus were determined in the Black Sea. A total of 306 individuals (170 female and 136 male) were caught between 2017 and 2018 with trammel nets. The mean length and the mean weight of the specimens were determined as 18.18 cm + 2.01 (Min: 15.7 cm-Max: 31.0 cm) and 79.16 g + 38.20 (Min: 49.23 g-Max: 393.8 g), respectively. The length-weight relationship was described for all individuals by the following formula W = 0.0147 L 2.947… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…More recent findings by [24] and [26] revealed the presence of this species on the South Coast of Crimea and near Cape Aya. Atlantic striped bream has also been reported on the coast of Türkiye [27][28][29]31,32,49] and off the Caucasus coast [25,50]. This species has been observed in the coastal waters of the southeastern Crimea, specifically within the protected region of the Karadag Nature Reserve [33].…”
Section: Resultsmentioning
confidence: 98%
“…More recent findings by [24] and [26] revealed the presence of this species on the South Coast of Crimea and near Cape Aya. Atlantic striped bream has also been reported on the coast of Türkiye [27][28][29]31,32,49] and off the Caucasus coast [25,50]. This species has been observed in the coastal waters of the southeastern Crimea, specifically within the protected region of the Karadag Nature Reserve [33].…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, fish species that settled in the Black Sea ecosystem with the effect of global climate change are in constant change (van der Voo, 1990;Aydın & Sözer, 2016;Aydın & Bodur, 2018;Zengin, 2019;Aydın, 2020;Karadurmuş et al, 2021b). John dory can increase the biomass level on the Turkish coast of the Black Sea and become a sustainable fishery resource within a productive habitat in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the b value was calculated as 3.003 for all individuals, and it being over three indicates that the sampled fish have sufficiently good environmental conditions and that total growth was achieved as required. In Turkey, most of the researchers (Türkmen & Akyurt, 2003;Akyol et al, 2007;Gökçe, Aydın, & Metin, 2007;İlkyaz, Metin, Soykan, & Kınacıgil, 2008;Emre et al, 2010;Acarlı, Kara, & Bayhan, 2014) have reported positive allometry growth for L. mormyrus whereas some of the researchers (Bilge, Yapıcı, Filiz, & Cerim, 2014;Sümer et al, 2014;Altın et al, 2015;Aydın, 2017;Aydın & Sözer, 2019;Reis & Ateş, 2020) have reported negative allometry growth. The relationship between a specimen length and its weight varies over time and between locations, depending on the abundance of food, temperature, salinity, or reproductive activity (Yankova, 2016).…”
Section: Charactersmentioning
confidence: 99%